Gut microbiome of the sole surviving member of reptile order Rhynchocephalia reveals biogeographic variation, influence of host body condition and a substantial core microbiota in tuatara across New Zealand - Carmen Hoffbeck; Danielle M. R. L. Middleton; Sarah K. Lamar; Susan N. Keall; Nicola J. Nelson; Michael W. Taylor (Ecology and Evolution, 2024)
Abstract Tuatara are the sole extant species in the reptile order Rhynchocephalia. They are ecologically and evolutionarily unique, having been isolated geographically for ~84 million years and evolutionarily from their closest living relatives for ~250 million years. Here we report the tuatara gut bacterial community for the first time. We sampled the gut microbiota of translocated tuatara at five sanctuaries spanning a latitudinal range of ~1000 km within Aotearoa New Zealand, as well as individuals from the source population on Takapourewa (Stephens Island). This represents a first look at the bacterial community of the order Rhynchocephalia and provides the opportunity to address several key hypotheses, namely that the tuatara gut microbiota: (1) differs from those of other reptile orders; (2) varies among geographic locations but is more similar at sites with more similar temperatures and (3) is shaped by tuatara body condition, parasitism and ambient temperature. We found significant drivers of the microbiota in sampling site, tuatara body condition, parasitism and ambient temperature, suggesting the importance of these factors when considering tuatara conservation. We also derived a ‘core’ community of shared bacteria across tuatara at many sites, despite their geographic range and isolation. Remarkably, >70% of amplicon sequence variants could not be assigned to known genera, suggesting a largely undescribed gut bacterial community for this ancient host species.